A psicanálise e o complexo de Édipo: (novas) observações a partir de Hamlet - SOUZA, Maurício Rodrigues de (2014)
This article is an exercise of comprehension of the Oedipal Complex in Psychoanalysis. Therefore, beyond tracing the development of the concept in the Freud's work, it takes the story of Hamlet as an illustrative device to testify through art the possible manifestations of the oedipian phenomenon. In conclusion, it also emphatises the possible inter-relations between psychoanalysis and tragedy.